Electrochemical pneumatic battery for untethered soft gripper - Li, Wanxin (Nanyang Technological University, 2023)
Metal-air batteries are an influential component of today's developments in green chemistry, while soft grippers are a major direction for future research in robotics. The main characteristic of the metal-air battery is that it performs the charging and discharging of the battery by absorbing and releasing oxygen. The most vital part of the research on soft body grippers is the choice of actuator, and pneumatic actuators are a good choice in terms of difficulty and efficiency of operation. Therefore, in this thesis, experiments are used to combine the both to study the actuation of the soft gripper by a metal-air battery. In the experiments carried out in this thesis, we designed two batteries in series based on a fivelayer structure, and then constructed a soft gripper combining a pneumatic grid structure actuator and a smart fabric. The combined metal-air battery is connected to the soft gripper with a hose to control the flow of gas through a valve and the battery is connected to an external power supply for charging and discharging. During the charging and discharging process the battery absorbs or releases oxygen causing the flexible gripper to bend and straighten, a phenomenon that is observed and based on which the gripping of objects is achieved. In conclusion, this thesis has designed and implemented a metal-air cell actuated soft gripper to capture objects, and has summarised and analysed the whole experiment, as well as providing an overview of future developments of the experiment.